Advanced Welding Methods and Equipment - Li, Ruifeng; Li, Taotao; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This book helps graduate students master welding theory, advanced welding technology and welding practice. With the continuous development and deepening of welding technology and the rapid development of computer science, the content of "Advanced Welding Methods" has also been expanded. It is divided into seven chapters, including laser welding, electron beam welding, friction stir welding, narrow gap welding, laser-arc hybrid welding, underwater welding, and development of the traditional welding process. The compilation of this book combines theory and practice, focusing not only on teaching and training theoretical knowledge, but also on integrating cases and providing practical training. Advanced Welding Methods and Equipment is a highly theoretical and practical course, which is an important link to improve students' welding practice ability and innovation ability. It is of great help for students to learn and understand welding technology. This book is used as a textbook for graduate students of related majors, and also as a reference for welding technology developers and researchers of related colleges and universities.
Laser welding -- Electron beam welding -- Friction stir welding -- Narrow gap welding -- Laser arc composite welding technology -- Underwater welding -- Cold metal transition welding -- Welding robots.
Keywords: Production engineering; Materials; Manufactures; Mechanical Process Engineering; Materials Engineering; Machines, Tools, Processes